ACCREDITATION AND STRATEGIC PLANNING: EXPERIENCE OF THE SCHOOL OF PSYCHOLOGY - Salazar Mora, Zaida (2006)
This article suggests that the evaluation and the credit validation in theUniversity of Costa Rica (UCR) have been valuable to improve quality.However, according to the experience of the School of Psychology, it isrequired to continue with a strategy that involves the goals and policies of theacademic units, establishing as well the actions to anticipate and respond to asituation of change and uncertainty. The strategy goes beyond the quality: itimplies innovation, systemic vision, plan making, plan execution, and plansupervision. It is required an innovative and entrepreneur university thatcarries, even more, its mission to the practice.